Beyond the status quo: BRICS+ and the challenge to the G7 - Günther Maihold (EconPol Forum, 2024)
Since the BRICS+'s challenge to the liberal international order has to do more with various particular issues than with an attempt to upend the norms that underpin the global order, the G7 should negotiate these issues in a step-by-step approach with the BRICS+. The G7 should accept the challenge presented by BRICS+ and establish the groundwork for a long-lasting dialogue with both the BRICS bloc and its individual member states. The BRICS+ expansion requires a great deal of openness on the part of the G7 to discuss and negotiate the pending issues of representation in the international financial organizations and the definition of positions regarding climate policy. The G7 countries are being challenged to come up with new, competitive concepts for development finance and cooperation that present a visible difference to China's offers of less conditional financial assistance. With regard to the BRICS+ members' strategy of multialignment and forum shopping, the G7 should provide integral responses to the demands presented in order to avoid a situation of diffuse challenges voiced in different international fora.
Keywords: 330